British Archaeology Abroad, 1966: British Institute of Archaeology at Ankara - Gough, Michael
Can Hasan; survey of prehistoric sites: Değirmen Özü near Ortaköy, Kayaardı Tepesi on the west side of the town of Niğde, and Tepecik-Çiftlik.